Validation of high-throughput sequencing-based test system for detection of microsatellite instability in colorectal cancer samples - A. A. Lebedeva; A. N. Taraskina; A. I. Kavun; E. V. Belova; T. V. Grigor'eva; O. A. Kuznetsova; D. A. Kravchuk; L. D. Belyaeva; V. E. Nikulin; E. D. Khomenko; V. A. Mileyko; A. A. Tryakin; et al. (Успехи молекулярной онкологии)
Introduction. Currently in routine clinical practice, standard methods based on polymerase chain reaction (PCR) and immunohistochemical examination are used to determine microsatellite instability (MSI) and deficient mismatch repair system (dMMR). MSI identification using high-throughput sequencing (next generation sequencing, NGS) is of special interest because it allows to analyze a large number of microsatellites and simultaneously study alterations in therapeutically significant genes.Aim. To validate of amplicon-based NGS panel for analysis of MSI and alterations in clinically significant genes in colorectal cancer.Materials and methods. High-throughput sequencing for MSI analysis was performed on formalin-fixed paraffinembedded (FFPE) samples from patients with colorectal cancer of any stage using amplicon-based panel “Solo-test Driver” (Russia) which covers 38 genes and 39 short tandem repeats (mononucleotides). As a reference method, 5-loci (BAT25, BAT26, NR21, NR24 and NR27) PCR was used. In NGS, MSI was evaluated based on κmer distribution. Statistical analysis was performed using Cohen’s kappa (κ), Mann-Whitney u test, and Fisher’s exact test.Results. An amplicon-based NGS panel for analysis of MSI in 39 loci and alterations in 39 genes was developed and validated on 160 archival FFPE samples of colorectal cancer. Per PCR, 42 (26.25 %) samples were MSI-positive, 118 (73.75 %) were MSI-negative. The results of PCR and NGS were concordant in 98.75 % (158/160) cases.Conclusion. The κ coefficient was 0.97 which demonstrates high concordance of MSI analyses using PCR and the developed NGS-based assay system.